2018
DOI: 10.1155/2018/7071383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drug Policy Changes on Evolution of Molecular Markers of Plasmodium falciparum Resistance to Chloroquine, Amodiaquine, and Sulphadoxine-Pyrimethamine in the South West Region of Cameroon

Abstract: Background As a result of the spread of parasites resistant to antimalarial drugs, Malaria treatment guidelines in Cameroon evolved from nonartemisinin monotherapy to artemisinin-based combination therapy. The aim of this study was to assess the effect of these therapy changes on the prevalence of molecular markers of resistance from 2003 to 2013 in Mutengene, Cameroon. Methodology Dry blood samples (collected in 2003–2005 and 2009–2013) were used for parasite DNA extraction. Drug resistance genes were amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 29 publications
5
36
0
Order By: Relevance
“…The double mutation was prevalent in Sudan in 2007 [30] and still maintains the double mutant genotype with an emerging triple mutation [31]. Triple mutants (51I, 59R, 108N), which associated with highlevel pyrimethamine resistance [10,11], were almost fixed in the African population [32,33]. High level of triple mutant genotypes was also found in the present study among isolates originates from Nigeria and Cameroon, which is in agreement with other studies [32,33].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The double mutation was prevalent in Sudan in 2007 [30] and still maintains the double mutant genotype with an emerging triple mutation [31]. Triple mutants (51I, 59R, 108N), which associated with highlevel pyrimethamine resistance [10,11], were almost fixed in the African population [32,33]. High level of triple mutant genotypes was also found in the present study among isolates originates from Nigeria and Cameroon, which is in agreement with other studies [32,33].…”
Section: Discussionsupporting
confidence: 90%
“…Triple mutants (51I, 59R, 108N), which associated with highlevel pyrimethamine resistance [10,11], were almost fixed in the African population [32,33]. High level of triple mutant genotypes was also found in the present study among isolates originates from Nigeria and Cameroon, which is in agreement with other studies [32,33]. Among the Indian sub-continent isolates, the double (59R/108N and 51I/108N) mutants genotypes were the most frequent genotypes followed by triple (51I/59R/108N) mutant genotypes, which are in agreement with previous reports from India [21,27,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the IC 50 of antimalarial drugs between parasite lines expressing wild type pfmdr1-Y184 or mutant 184F were shown to be closely linked to either of pfmdr1 N86 or 86Y alleles and not the 184F allele [53]. However, several epidemiological studies on the prevalence of pfmdr1 Y184F polymorphisms have shown that the Y184 allele is predominantly con ned to East and Central Africa while the mutant 184F allele predominates in West Africa [1,32,36,48]. Indeed, reports of the high occurrence of the mutant pfmdr1 184F in West Africa were corroborated by the present ndings in which we show that the prevalence of pfmdr1 184F was high in all the states, and especially in Kano, and that its prevalence is higher in North-West compared to North-East Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports from Africa have suggested that linkage between pfmdr1 N86Y/Y184F/D1246Y results in haplotypes with particular phenotypic characteristics that may be selected depending on the particular drugs that the population is exposed to [50][51]. The occurrence of pfmdr1 NFD and NYD haplotypes, for example, may result from AL selection while the pfmdr1 YYY haplotype may be favoured in regions where parasites are exposed to AS-AQ, DHAP and CQ [15,32]. The treatment of uncomplicated malaria with AL often selects pfmdr1 haplotypes bearing the N86 allele [29,48].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in malaria treatment policies greatly influence the frequency of mutations that modulate P. falciparum susceptibility to anti-malarial drugs, including Pfmdr1 N86Y [31]. The introduction of ACT in the early 2000s and cessation of chloroquine use in the 1990s led to drastic changes in Pfmdr1 N86Y allele frequency in various malaria-endemic settings [27,33,34]. For instance, the frequency of Pfmdr186Y has declined dramatically, in favour of Pfmdr1 N86, in countries, where AL is used as the first−line treatment for malaria.…”
Section: Discussionmentioning
confidence: 99%